A New Congestion Control Mechanism for WSNs - Michopoulos, V; Guan, L; Phillips, I (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
Congestion in Wireless Sensor Networks (WSN) can be a severe problem, as it causes a plethora of malfunctions such as packet loss, lower throughput, energy inefficiency, and short lifetime. As a result, the performance of the whole network is subject to undesirable change; an issue that renders congestion control an issue of uttermost importance for such networks. As far as data-collection applications in WSN are concerned, normal Internet-style definitions of fairness may not apply. All data sources must have identical access to the entire network bandwidth so as to enable the application to have a complete picture of the monitored area. Furthermore, the limited battery power as well as limited memory and processing resource of sensor nodes, do not allow them to execute complex algorithms. This paper describes a new congestion control mechanism. In our mechanism, the buffer in each node is adjusted according to the transmitting downstream nodes in order to minimize packet drop; the algorithm automatically adjusts a node's forwarding rate to avoid packet drops due to congestion. The algorithm resolves the fairness problem by allocating equal bandwidth to the sources. Moreover, the fact that it can be implemented without large resource requirements, renders it suitable for WSNs. It can also detect congestion preventively and adjust the transmission rates of the nodes in order to eliminate congestion with minimal loss. Simulation results show significant improvements in terms of throughput compared to previous works.